2020
DOI: 10.1002/art.41312
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of JNK Enhances Senescence in Joint Tissues and Increases the Severity of Age‐Related Osteoarthritis in Mice

Abstract: Objective. To determine the role of JNK signaling in the development of osteoarthritis (OA) induced by joint injury or aging in mice. Methods. In the joint injury model, 12-week-old wild-type control, JNK1 −/− , JNK2 −/− , and JNK1 fl/fl JNK2 −/− aggecan-Cre ERT2 double-knockout mice were subjected to destabilization of the medial meniscus (DMM) (n = 15 mice per group) or sham surgery (n = 9-10 mice per group), and OA was evaluated 8 weeks later. In the aging experiment, wildtype control, JNK1 −/− , and JNK2 −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
1
17
1
Order By: Relevance
“…It has been reported that ROS exert the inflammatory effects through the activation of the JNK pathway (Lo et al, 1996). The role of the JNK pathway in the regulation of catabolic gene expression in chondrocytes has also been confirmed previously by us using a JNK-specific inhibitor (Akhtar and Haqqi, 2011;Haseeb et al, 2017) and by others using a knockout mouse model of JNK (Ismail et al, 2016;Loeser et al, 2020). In this study, we demonstrate, for the first time, that mitochondrial dysfunction increases the expression of COX-2, IL-6, MMPs and ADAMTS5 through the activation of the JNK pathway in human chondrocytes.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that ROS exert the inflammatory effects through the activation of the JNK pathway (Lo et al, 1996). The role of the JNK pathway in the regulation of catabolic gene expression in chondrocytes has also been confirmed previously by us using a JNK-specific inhibitor (Akhtar and Haqqi, 2011;Haseeb et al, 2017) and by others using a knockout mouse model of JNK (Ismail et al, 2016;Loeser et al, 2020). In this study, we demonstrate, for the first time, that mitochondrial dysfunction increases the expression of COX-2, IL-6, MMPs and ADAMTS5 through the activation of the JNK pathway in human chondrocytes.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, 65–90% of differentially expressed genes may be unique to primary versus secondary OA. Additionally, transgenic animal models have revealed that several genes are differentially involved in the progression of primary and secondary OA [ 4 – 9 ]. For example, deletion of Panx3 protects against surgically induced OA yet dramatically worsens primary OA [ 4 ] and deletion of JNK1/2 accelerates the development of primary OA while having no effect on surgically induced OA progression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, deletion of Panx3 protects against secondary OA yet dramatically worsens primary OA (4), and deletion of JNK1/2 accelerates the development of primary OA while having no effect on secondary OA progression (9). Together, these studies reinforce that unique mechanisms underpin these two forms of OA.…”
Section: Introductionmentioning
confidence: 87%
“…Only 10% of differentially upregulated and 35% of differentially downregulated genes in OA vs non-OA samples are conserved between primary and secondary OA, meaning 65-90% of differentially expressed genes are unique to primary versus secondary OA 2 . Additionally, transgenic animal models have revealed that several genes are differentially involved in the progression of primary and secondary OA [3][4][5][6][7][8] . For example, deletion of Panx3 protects against secondary OA yet dramatically worsens primary OA 3 , and deletion of JNK1/2 accelerates the development of primary OA while having no effect on secondary OA progression 8 .…”
Section: Introductionmentioning
confidence: 99%